Avaliação das incertezar no impacto ambiental da produção de cana-de-açúcar decorrente da substituição de combustíveis fósseis por biocombustíveis - Duarte, Ricardo Geraldini de Almeida (Universidade Federal de São Carlos, 2024)
This study aims to quantify and analyze the environmental impact associated with sugarcane production, with an emphasis on the Global Warming Potential (GWP) throughout the stages of planting, harvesting, and transportation. Using the RenovaCalc program database and the EMSO process simulator, computational modeling was performed to quantify greenhouse gas emissions, expressed in kgCO2eq/tcane. Considering that Life Cycle Assessment (LCA) depends on input consumption, which varies among producing industries, this study applied the Monte Carlo method to conduct an uncertainty analysis, accounting for variations in the consumption of raw materials and fuels across different mills in Brazil. In addition to the uncertainty analysis, a global sensitivity analysis was performed to identify the variables that most influence the variation in sugarcane GWP. The models were also used to evaluate the effects of replacing conventional fuels with more sustainable alternatives, such as biodiesel, in sugarcane transportation and agricultural machinery, aiming to reduce the environmental impact of sugarcane production and, consequently, the final products, such as ethanol and sugar. The results indicated a substantial variation in the environmental impact of sugarcane, estimated at 48.36 ± 8.7 kgCO2eq/tcane. The global sensitivity analysis revealed that the consumption of synthetic nitrogen fertilizers is the main source of variation in emissions. Moreover, the complete replacement of fossil diesel with biodiesel allows for a reduction of approximately 20% in sugarcane production emissions. These findings provide valuable insights for adopting agricultural practices with lower environmental impact and thus reducing the environmental footprint of ethanol.
Assessment of uncertainty in the environmental impact of sugarcane production resulting from the replacement of fossil fuels with biofuels
Keywords: Cana-de-açúcar; Emissões; Análise de incerteza; Biocombustíveis; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA